2017
DOI: 10.1186/s12941-017-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of felt demand for dengue vaccines in the North Caribbean region of Colombia

Abstract: BackgroundThe increasing burden associated with dengue in Latin America makes it essential to understand the community’s interest in acquiring vaccines, as an input to plan its introduction in endemic regions. The objective of this study is to learn the felt demand for dengue vaccines by estimating the willingness to pay and its associated factors in endemic communities of the North Caribbean region of Colombia.MethodsA population survey was administered from October to December 2015, including 1037 families i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…Nevertheless, there is no significant association between WTP for dengue vaccine with knowledge of dengue. This finding is contrary to several of the studies of WTP for dengue vaccine conducted previously which showed significant association between knowledge of dengue with WTP for dengue vaccine (Bracho-Churio et al, 2017;Hadisoemarto & Castro, 2013;Harapan et al, 2017;Lee et al, 2015). These studies reported that knowledge have a significant association with WTP for dengue vaccine where good knowledge is related to a higher WTP for dengue vaccine.…”
Section: Ijphcscontrasting
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, there is no significant association between WTP for dengue vaccine with knowledge of dengue. This finding is contrary to several of the studies of WTP for dengue vaccine conducted previously which showed significant association between knowledge of dengue with WTP for dengue vaccine (Bracho-Churio et al, 2017;Hadisoemarto & Castro, 2013;Harapan et al, 2017;Lee et al, 2015). These studies reported that knowledge have a significant association with WTP for dengue vaccine where good knowledge is related to a higher WTP for dengue vaccine.…”
Section: Ijphcscontrasting
confidence: 99%
“…Higher income category is associated with high WTP for dengue vaccine (χ2=11.974, p=0.003). This finding coincides with all studies of WTP for dengue vaccine done which reported a highly significant association between WTP for dengue vaccine with monthly household income of respondents (Bracho-Churio et al, 2017;Godói et al, 2017;Hadisoemarto & Castro, 2013;Harapan et al, 2017;Lee et al, 2015;Palanca-Tan, 2008).…”
Section: Ijphcssupporting
confidence: 91%
See 3 more Smart Citations